Analisis Butir Soal Ulangan Semester Ganjil Mata Pelajaran Matematika Kelas VIII SMP - Khairil Basri; Baidowi Baidowi; Junaidi Junaidi; Muhammad Turmuzi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to know the quality of Grain Analysis of Odd Semester Test Questions Of Mathematics Subjects Grade VIII at State Junior High School 1 Kediri In The Academic Year 2018/2019 which is reviewed in terms of Validity, Reliability, Difficulty Level, Differentiating Power, and Effectiveness of Phishing. This is a descriptive research. The result of this research shows that: in terms of Validity, the amount of valid questions up to 14 points of the question (70%) and invalid question are up to 6 points of question (30%); in terms of Reliability, including questions that have high reliability is with a coefficient 0.79; in terms of Difficulty Level, the number of questions that are include in the difficult categorythere are 2 points (10%), which belongs to the moderate category there are 17 items (85%), and include in easy category there is 1 item(5%); in terms of Differentiating power, the number of problems categorized as very bad as 1 item (5%), bad category as much as 1 item (5%), categorized enough as many as 9 points (45%), good category as much as 6 items (30%) and very high category 3 items (15%); reviewed in terms of Effectiveness of phishing, there are 15 points of question (75%) with excellent outwits, 5 points of question (25%) with a good phishing, 0 point problem (0%) with a less bad phishing and with a bad phishing 0 point problem (0%).